Linear IgA bullous dermatosis - Dmochowski, Marian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
In this comprehensive review, linear IgA bullous dermatosis (LABD) is discussed according to current understanding of the molecular nature of this disease. The identification of the autoantigen in lamina lucida type of LABD as the shed form of BP180 is the main investigative achievement of LABD studies in the last decade.